Healthy eating for better living : a manual on nutrition and HIV/AIDS for healthcare workers in the Caribbean (CFNI MonaJM, 2004)
Provides technical yet practical information for professionals involved in the practice and teaching of nutrition and HIV/AIDS at all levels.
Keywords: NUTRITION